A239 QUALITATIVE EVALUATION OF THE DECISIONS AND EXPERIENCES OF PEOPLE WHO INJECT DRUGS WHO RECEIVED A LIVER DISEASE ASSESSMENT AS PART OF A LIVER HEALTH PROMOTION CAMPAIGN: THE LIVERLIFE STUDY. (1st March 2018) - Marshall, A D; Treloar, C; Dore, G J; Grebely, J
Abstract: Background: A liver health promotional campaign took place in New South Wales, Australia (May to October 2014), with 235 people who inject drugs (PWID) receiving FibroScan®-based disease assessment. Participant follow-up occurred 2–16 weeks post-enrolment. Aims: The aim of this qualitative sub-study was to evaluate the decisions and experiences of participants who received a liver disease assessment, including interpretation of FibroScan® score and subsequent health behaviours. Methods: Participants were recruited from two opioid substitution treatment clinics and one medically supervised injecting centre between November 2015 and February 2016. The four recruitment categories were: a) high FibroScan® score (≥9.5 kPa)/ attended LiveRLife follow-up; b) high score/did not attend follow-up; c) low score (≤9.4 kPa)/attended follow-up; and d) low score/did not attend follow-up. Participants were not reminded of their category during recruitment. Inclusion criteria were: participation in the LiveRLife campaign, received a FibroScan® score, and informed written consent. Interviews were audio-taped and transcribed verbatim. Data was analysed using thematic analysis. Results: Of 33 semi-structured interviews [category a (12 participants); category b (2); category c (11); category d (8); 21% female], reasons for wanting to receive a FibroScan® were varied. Most participants interpreted their level of liver disease correctly based on their recalled FibroScan® score. Persons with higher scores frequently recalled feeling shocked by their score (e.g. 'wake-up call') whereas participants with lower scores were typically pleasantly surprised (e.g. incentive to keep liver healthy). Some positive health changes were stated with several relating their score to hepatitis C treatment. Additionally, some confusion regarding causes of increased liver disease persisted despite this information being provided in the campaign. Further analyses will explore health-seeking behaviours (or lack thereof) by category. Conclusions: Results provide greater insight into strategies to enhance knowledge and 'linkage to care' for PWID with, and at-risk of, advanced liver disease. Funding Agencies: The study was funded from MSD, Australia.